Observing non-classical crystallisation processes in gypsum via infrared attenuated total reflectance spectroscopy. Issue 1 (2nd November 2016) - Stach, R.; Krebs, P.; Jones, F.; Mizaikoff, B.
Abstract : The nature of crystallisation processes is of major interest, as they are among the most frequently occurring reactions associated with a variety of relevant processes in chemistry, biochemistry, and geochemistry. Abstract : The nature of crystallisation processes is of major interest, as they are among the most frequently occurring reactions associated with a variety of relevant processes in chemistry, biochemistry, and geochemistry. In this study, an innovative approach towards fundamentally understanding crystallisation pathways in a seemingly simple system – gypsum – has been developed via infrared spectroscopic techniques. Specifically, infrared attenuated total reflection spectroscopy (IR-ATR) was instrumental in revealing detailed information on inter- and intramolecular interactions during gypsum crystallization via subtle changes in the vibrational spectra of the involved reactants. When applying D2 O as an isotope marker, it was shown that isotopically labelled water may serve as a viable spectroscopic probe during mid-infrared (3–15 μm) studies providing unique insight into the crystallization process at molecular-level detail. In addition, it was revealed that H2 O and D2 O give rise to distinctly different reaction kinetics during the crystallization process.